Effect of Trastuzumab–HER2 Complex Formation on Stress-Induced Modifications in the CDRs of Trastuzumab - Spanov, Baubek; Aboagye, Victoria; Olaleye, Oladapo; Govorukhina, Natalia; van de Merbel, Nico C.; Bischoff, Rainer (Frontiers in Chemistry, 2022)
Asparagine deamidation and aspartic acid isomerization in the complementarity determining regions (CDRs) of monoclonal antibodies may alter their affinity to the target antigen. Trastuzumab has two hot spots for deamidation and one position for isomerization in the CDRs. Little is known how complex formation with its target antigen HER2 affects these modifications. Modifications in the CDRs of trastuzumab were thus compared between the free antibody and the trastuzumab-HER2 complex when stressed under physiological conditions at 37oC. Complex formation and stability of the complex upon stressing were assessed by size-exclusion chromatography. Deamidation of Light-chain Asn-30 (Lc-Asn-30) was extensive when trastuzumab was stressed free but reduced about 10-fold when the antibody was stressed in complex with HER2. Almost no deamidation of Heavy-chain (Hc-Asn-55) was detected in the trastuzumab-HER2 complex, while deamidation was observed when the antibody was stressed alone. Hc-Asp-102 isomerization, a modification that critically affects biological activity, was observed to a moderate degree when the free antibody was stressed but was not detected at all in the trastuzumab-HER2 complex. This shows that complex formation has a major influence on critical modifications in the CDRs of trastuzumab.